Monosexual Cercariae of Schistosoma japonicum Infection Protects Against DSS-Induced Colitis by Shifting the Th1/Th2 Balance and Modulating the Gut Microbiota - Zhou, Hongli; Zeng, Xiaojing; Sun, Dongchen; Chen, Zhe; Chen, Weixin; Fan, Liwei; Limpanont, Yanin; Dekumyoy, Paron; Maleewong, Wanchai; Lv, Zhiyue (Frontiers in Microbiology, 2021)
Inflammatory bowel disease (IBD)-related inflammation is closely associated with initiation and progression of colorectal cancer. Generally, IBD is treated with 5-aminosalicylic acid and immune-modulating medication. However, side effects and limitations of these therapies are emerging; thus, developing novel preventative or therapeutic approaches is imperative. Here, we constructed a dextran sodium sulfate (DSS)-induced IBD mouse model followed by monosexual Schistosoma japanicum cercariae (mSjci) infection at day 1 or dexamethasone (DXM) administration from day 3 to day 5 as a positive control. The protective effect of mSjci on IBD mice was evaluated through their clinical signs, histopathological lesions and intestinal permeability assessment. To uncover the underlying mechanism, the Th1/Th2 balance and Treg cell population were also examined. Additionally, gut microbiota alteration was also tested to investigate the interaction between the mSjci-modulated immune response and pathogenic microbiome. Mice treated with DSS and mSjci showed less IBD clinical signs and less impaired intestinal permeability than DSS treatment. Mechanistically, mSjci modulated the Th1/Th2 balance by repressing IFN-γ production, promoting IL-10 expression and enhancing the Treg subset population. Moreover, mSjci dramatically reshaped the gut microbiota community structure, diversity and richness and subsequently exerted immune-modulating effects. Our findings provide evidence that mSjci might serve as a novel and effective protective strategy and the gut microbiota might be a new therapeutic target for IBD.